A Novel Homozygous Frameshift Variant in DYM Causing Dyggve-Melchior-Clausen Syndrome in Pakistani Patients - Gaboon, Nagwa E. A.; Parveen, Asia; Ahmad, Khaled A.; Shuaib, Taghreed; Al-Aama, Jumana Y.; Abdelwehab, Lereen; Arif, Amina; Wasif, Naveed (Frontiers in Pediatrics, 2020)
Background Dyggve-Melchior-Clausen syndrome (DMC) is a skeletal dysplasia with associated defects of brain development and intelligence. The truncating pathogenic variants in DYM are the most frequent cause of DMC. Smith-McCort (SMC), another skeletal dysplasia, is also caused by nonsynonymous DYM variants. Methods and Results In the current study, we examined a Pakistani consanguineous family with three affected members. Clinical features like spondyloepimetaphyseal dysplasia, indicative of characteristic skeletal abnormalities, and intellectual disability were observed. Our male patients had microcephaly and coarse facial features while the female patient did not represent microcephaly or abnormal facies, which are significant features of DMC patients. Sanger sequencing identified a novel homozygous frameshift insertion (c.95_96insT, p.W33Lfs*14) in DYM, which likely leads to nonsense-mediated decay (NMD). Conclusion The novel frameshift change verifies the fact that pathogenic variants in DYM are the most frequent cause of DMC.